Pattern of fiber intake in different socio-demographic settings among elderly in Jakarta, Indonesia and its associated factors - Nanda Fauziyana; Erfi Prafiantini; Novi Silvia Hardiany (Indonesian Nutrition Association, 2021)
Introduction Despite many health benefits from dietary fiber, inadequate intake is prevalent among elderly population. This study aims to obtain the pattern of fiber intake in different socio-demographic backgrounds among elderly in Jakarta area, Indonesia and its’ associated factors. Methods: A cross-sectional study was conducted among elderly aged > 60 years in 5 community health center across Jakarta province. A total of 126 elderly were interviewed using two non-consecutive 24-h dietary recall methods to obtain dietary intake data. Socio-demographic backgrounds on age, sex, education, income, marital status, and energy intake were assessed using structured questionnaire. Mann-Whitney or independent t-test was performed to measure the different of fiber intake in each socio-demographic variable. Linear regression test was performed to analyze the variables that associated with fiber intake. Results: Majority of 98.4% of elderly have total fiber intake <80% of Indonesian Recommended Dietary Allowance (RDA) with average intake of 6.6 g/d. Lower fiber intake was significantly found in females, widowed/separated, have lower education and income, and have inadequate energy intake. Factors associated with total fiber intake were income (adjusted β=0.20, p=0.01) and energy intake adequacy (adjusted β=0.65 p=0.00). Conclusion: Fiber intake among elderly in urban area is inadequate and the pattern was worse in the low socio-demographic settings. By this finding, it is important to give priority to the socially disadvantages group when formulating nutrition intervention policy in this population setting.